Development of QSAR model to predict the ecotoxicity of Vibrio fischeri using COSMO-RS descriptors - Abdul Mutalib, Mohamed Ibrahim (2017)
Ionic liquids (ILs) are class of solvent whose properties can be modified and tuned to meet industrial requirements. However, a high number of potentially available cations and anions leads to an even increasing members of newly-synthesized ionic liquids, adding to the complexity of understanding on their impact on aquatic organisms.